Determining Factors in the Use of Digital Marketing and Its Effect on Marketing Performance in the Creative Industries in Tasikmalaya - Gunawan, Gun Gun; Sulaeman, Maman (Budapest International Research and Critics University, 2020)
The economic development of creative industries is an important aspect as a potentially good force for the national economy for the future. However, the creative industry in Tasikmalaya lacks product innovation, still maintaining the authenticity of its products by 67%, products that are easily replicated by 83%. Utilization of digital marketing concepts provides hope for MSMEs to develop into economic power centers. This research aims to analyze the determining factors of digital marketing usage and its influence on digital marketing in the creative industries in Tasikmalaya. This research is categorized as explanatory research which is a study that aims to explain the causal relationship between variables through hypothesis testing. The Inference Statitic method used in the analysis of this research data is the path of analysis. The results showed knowledge of ICT (Information and Communication Technology) adoption had a significant effect on digital marketing. Innovation has a significant impact on digital marketing. Digital marketing is influenced by the knowledge of ICT adoption and Innovation. Knowledge of ICT adoption and innovation affects digital marketing through digital marketing.